ANALYSIS OF THE IMPLEMENTATION OF SAPTA PESONA IN THE MANGROVE TRACKING ATTRACTION, KARIMUNJAWA ISLANDS, JEPARA REGENCY - Muchammad Satrio Wibowo; Atika Nur Hidayah; Yesa Natali R Tampubolon; Aurel Filadelfia Saviola (Politeknik Pariwisata Makassar, 2025)
Mangrove forests, with their unique ecological characteristics and biodiversity, hold significant potential for tourism development through activities such as tracking, flora and fauna observation, and educational tours. In Karimunjawa, a mangrove tracking attraction is located on Kemujan Island. The application of Sapta Pesona principles plays a crucial role in shaping visitor experiences, influencing tourist arrivals, and contributing to the welfare of local communities engaged in tourism. This study aims to analyze the implementation of Sapta Pesona in the Mangrove Tracking attraction. Employing a descriptive quantitative approach, data were collected through observation and interviews, and subsequently analyzed using a Likert-scale scoring technique. Findings indicate that the average scores for each Sapta Pesona element are as follows: safety (2.7/less), orderliness (3.5/sufficient), cleanliness (2.6/less), coolness (3.7/sufficient), beauty (3.3/sufficient), friendliness (2.7/less), and memorability (1.0/very poor). The overall average score of 2.7 falls within the “less” category. These results highlight the need for collaborative efforts among stakeholders to strengthen Sapta Pesona implementation, ensure environmental sustainability, and foster community engagement in delivering quality tourism experiences in the Mangrove Tracking area in Karimunjawa Island